Pesan Edukasi Seksual bagi Remaja Tengger Melalui Tari Sodoran - Sony Sukmawan; Asri Kamila Ramadhani; Elvin Nuril Firdaus (Gondang: Jurnal Seni dan Budaya, 2020)
An open talk about sexual matters has become a taboo thing for most societies, and it is no exception for Tenggerese society. Through the internalization of traditions, Tengger ancestors gave their encoded message to children and adolescents on the subject of life, including sexual issues. The symbolism of sexual education was beautifully and courteously transmitted through the dance gestures of the Sodoran Dance. This research aimed to reveal the symbolic messages of the Sodoran dance that employs folklorism approaches and cultural studies. The collecting and analysis of data are done by ethnographic to unfold deeply and holistic to the culture of the Tenggerese people through the presentation of their view of life. This research shows that every part of the Sodoran dance represents the origin of human life which is from male and female meetings, marriage, birth, until the journey of human life. The Tenggerese adolescents’ exposure in the dance is reflected cultural transmission tendencies, a form of recognition, learning, and an expression of room in culture to grow more and more love of culture. More specifically, Sodoran dance is essentially a form of sexual education for the Tenggerese adolescents.